Utilization of breast MRI and breast MRI-guided biopsy in clinical practice: results of a survey in Québec and France - Mesurolle, Benoît (Insights Imaging, 2020)
BACKGROUND: To investigate the practice regarding breast MRI exams and breast MRI-guided biopsies in two countries with different health care systems, France and Québec. A 12-item questionnaire was distributed online among radiologists from France and Québec, attempting to determine: demographic characteristics and breast MRI diagnostic and MRI-guided practices (indications, workload, availability, and waiting time assessment). RESULTS: One hundred and seventy radiologists (France, 132 respondents (28.5%); Quebec, 38 respondents (35.2%)) participated in the survey, most of them based in non-academic centers. Thirty-eight percent of Quebec and 2.3% of French radiologists did not perform breast MRI in their daily practice. Nearly 50% of French and Quebec respondents interpreted 1–10 breast MRI exams per week. Decision-making factors of preoperative MRI were similar in both countries (pathology, age, and breast density), with a heavier emphasis placed on the surgeon’s opinion in Quebec (47.8% versus 21.8% (p = 0.009)). Quebec demonstrated a higher waiting time than France (1–2 weeks in 40% versus less than 1 week in 40%). MRI-guided breast biopsies (less than 5 MRI-guided biopsies per week) were being performed by a minority of the respondents (36% in France and 43% in Québec). CONCLUSION: Most of radiologists performing breast MRIs work in non-academic institutions in both countries. Waiting time is higher in Quebec, but most of preoperative breast MRIs are performed within 3 weeks in both countries. The surgeon plays an important role in recommending preoperative MRI in Quebec. MRI-guided breast biopsies are not widely available in both countries.